2014
DOI: 10.1128/jvi.02601-13
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocytes from Patients with a Hypomorphic Mutation inSTAT3Resist Epstein-Barr Virus-Driven Cell Proliferation

Abstract: E pstein-Barr virus (EBV) is an oncovirus that infects B cells and epithelial cells (1-3). EBV establishes lifelong latency in memory B lymphocytes; periodic activation into the lytic cycle can lead to asymptomatic shedding of virus in saliva. Upon infection of primary B cells, EBV must first drive cell proliferation in order to establish latency (3). Latency contributes to viral persistence. Although most of mankind is persistently infected with EBV, only a small fraction develops EBV-related cancers of B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…1 B and C). This increase in infected, foci-positive AD-HIES nuclei relative to healthy subject-derived nuclei agreed with our earlier observation that EBV-infected AD-HIES-derived B cells accumulate in the S phase and likely do not undergo transformation (19). Of note, although an increase in RPA protein (Fig.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…1 B and C). This increase in infected, foci-positive AD-HIES nuclei relative to healthy subject-derived nuclei agreed with our earlier observation that EBV-infected AD-HIES-derived B cells accumulate in the S phase and likely do not undergo transformation (19). Of note, although an increase in RPA protein (Fig.…”
Section: Resultssupporting
confidence: 79%
“…We previously reported that an early event such as EBV-binding or internalization results in activation and increased expression of cellular STAT3 in primary B lymphocytes. STAT3 then critically contributes to cell proliferation and transformation by promoting cell survival and relaxing the intra-S phase cell-cycle checkpoint (19). We now find that STAT3 contributes to intra-S phase checkpoint relaxation by suppressing signaling downstream of the critical S phase kinase ATR despite detection of replication stress-associated DNA damage that results from EBV infection.…”
Section: Significancementioning
confidence: 62%
See 2 more Smart Citations
“…This study and our earlier studies demonstrate that, in addition to phosphorylation and dimerization of STAT3, modulation of the protein level of STAT3 also regulates its function (22,30,(37)(38)(39). Our data also indicate that STAT3 functions at least partly by repressing the immediate-early gene product RTA, the key latency-to-lytic-phase viral switch.…”
Section: Discussionsupporting
confidence: 59%